Physiological Study of Stenotrophomonas maltophilia DHHJ in Feather Biodegradation：Structural Remodeling of Cell Surface and Dynamic Change in Kerastinase Activity - 曹张军 张卫 蒋晶君 龚润 张云龙 (东华大学学报（英文版）, 2017)
Poultry industry produces a vast amount of feather waste annually, which forms a burden for environment protection.However, feathers are valuable bio-resources with high keratinaceous protein content and can be converted into more valuable materials through some approaches such as biodegradation by microorganism-derived keratinases. The characters of keratinases in microorganisms remain largely undetermined. In this study,it is reported that the morphological change of cell surface and the activities of intracellular and extracellular keratinases in Stenotrophomonas maltophilia（ S. maltophilia） DHHJ. S. maltophilia DHHJ was cultured on lysogeny broth（ LB） and feather broth（FB） through fermenter technology,and ultrastructure of cell and keratinase activity including extracellular and intracellular enzyme were observed respectively. Ultrastructural change on the cell surface was only observed for the bacteria cultured on FB medium,but not on LB,suggesting that the change could be induced by feather keratin. Therefore, the results showed that extracellular keratinase is a kind of induction enzyme while intracellular keratinase is a kind of constitute enzyme in S. maltophilia DHHJ.